Simplified speciation and atmospheric volatile organic compound emission rates from non‐aerosol personal care products. (26th February 2020) - Yeoman, Amber M.; Shaw, Marvin; Carslaw, Nicola; Murrells, Tim; Passant, Neil; Lewis, Alastair C.
Abstract: Volatile organic compounds (VOCs) emitted from personal care products (PCPs) can affect indoor air quality and outdoor air quality when ventilated. In this paper, we determine a set of simplified VOC species profiles and emission rates for a range of non‐aerosol PCPs. These have been constructed from individual vapor analysis from 36 products available in the UK, using equilibrium headspace analysis with selected‐ion flow‐tube mass spectrometry (SIFT‐MS). A simplified speciation profile is created based on the observations, comprising four alcohols, two cyclic volatile siloxanes, and monoterpenes (grouped as limonene). Estimates are made for individual unit‐of‐activity VOC emissions for dose‐usage of shampoos, shower gel, conditioner, liquid foundation, and moisturizer. We use these values as inputs to the INdoor air Detailed Chemical Model (INDCM) and compare results against real‐world case‐study experimental data. Activity‐based emissions are then scaled based on plausible usage patterns to estimate the potential scale of annual per‐person emissions for each product type (eg, 2 g limonene person −1  yr −1 from shower gels). Annual emissions from non‐aerosol PCPs for the UK are then calculated (decamethylcyclopentasiloxane 0.25 ktonne yr −1 and limonene 0.15 ktonne yr −1 ) and these compared with the UK National Atmospheric Emissions Inventory estimates for non‐aerosol cosmetics and toiletries.